1999
DOI: 10.1016/s0009-9236(99)90084-x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of age on the pharmacokinetics and pharmacodynamics of midazolam

Abstract: These results suggest that the lower doses needed to reach sedation in the elderly subjects were attributable to a 50% decrease in EC50, not to changes in pharmacokinetics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
59
0
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(71 citation statements)
references
References 28 publications
7
59
0
2
Order By: Relevance
“…The same results were obtained with regards to gender (P>0.05). These data suggest that midazolam pharmacokinetics in Chinese after oral administration are unaffected by either age or gender, and this conclusion is consistent with studies of Caucasian subjects [34][35][36][37] . As an oral hypnotic, midazolam has been in the market for many years in China; however, there have been few pharmacokinetic studies [25][26][27] , and there is significant inter-study variability (Table 5).…”
Section: Midazolam Pharmacokinetics In Chinese After Oral Adminis Trasupporting
confidence: 89%
See 1 more Smart Citation
“…The same results were obtained with regards to gender (P>0.05). These data suggest that midazolam pharmacokinetics in Chinese after oral administration are unaffected by either age or gender, and this conclusion is consistent with studies of Caucasian subjects [34][35][36][37] . As an oral hypnotic, midazolam has been in the market for many years in China; however, there have been few pharmacokinetic studies [25][26][27] , and there is significant inter-study variability (Table 5).…”
Section: Midazolam Pharmacokinetics In Chinese After Oral Adminis Trasupporting
confidence: 89%
“…Investigation of the effects on midazolam pharmacokinetics using the PBPK model Previous studies in Caucasians demonstrated that the pharmacokinetics of midazolam were unaffected by age [34][35][36][37] ; however, this topic has never been examined in Chinese. In this study, the verified PBPK model was used to investigate the effects of age on midazolam pharmacokinetics in Chinese from a physiological perspective.…”
Section: Midazolam Pbpk Modelingmentioning
confidence: 99%
“…The EC 50 for sedation after intravenous midazolam is reduced by 50% in older people (522 Ϯ 236 versus 223 Ϯ 56 ng/ml) despite the absence of significant age-related pharmacokinetic differences (clearance, 399 Ϯ 91 versus 388 Ϯ 97 ml/min) (Albrecht et al, 1999). Similar age-related reductions in EC 50 for sedative and cognitive effects of benzodiazepines, in the absence of major pharmacokinetic changes, have been reported for flunitrazepam (Kanto et al, 1981).…”
Section: The Aging Process and Pharmacodynamic Responsesmentioning
confidence: 99%
“…Elderly individuals are generally more sensitive to pharmacotherapy although bidirectional pharmacodynamic alterations have been observed (Mangoni and Jackson, 2003). The central nervous system is especially vulnerable with aging and centrally acting drugs consistently shown to produce sensitized reactions in the elderly independent of pharmacokinetic changes include benzodiazepines (midazolam), opioids (morphine), and anticholinergic tricyclic antidepressants (imipramine and amitriptyline) (Albrecht et al, 1999;Lotrich and Pollock, 2005;Villesen et al, 2007). Mechanisms by which these pharmacodynamic alterations occur are still relatively unclear but are usually attributed to changes in drug-receptor interactions, altered postreceptor signaling, and impaired homeostatic mechanisms (Shi et al, 2008).…”
Section: Introductionmentioning
confidence: 99%